Market Implications of Integration of Asian Rice Markets - Furuhashi, Gen (OECD Food, Agriculture and Fisheries Papers, 2017)
This paper explores how the integration of rice markets in ASEAN countries influences the import, export, production, consumption, and prices of rice in those countries, as well as in the rest of the world. The analysis describes current policies applied to ASEAN rice markets, then evaluates the ten-year impacts of two reform scenarios using the OECD-FAO Aglink-Cosimo model. The first scenario involves the elimination of tariffs within the region, while protection vis-à-vis countries outside the region remains unchanged. The second scenario involves closer price integration across the region, again with protection versus countries outside the region unchanged. The analysis finds that opening up the regional trade market will lead to greater overall production, consumption and trade across the region. The overall welfare gains are over fifteen times higher with full price integration, as opposed to just tariff reform. Significant price changes create winners and losers within all countries, underscoring the need for complementary policies to accompany a rice market integration agenda